The Clash of Civilization: A Prognosis of the Future or the Lure of the Past - Abdullah, Taufik (P2KK LIPI, 1997)
The story begins when Samuel P. Huntington – the famous political scientist from a highly prestigious university, Harvard University and a citizen of the strongest power on earth – write an articles, entitled “The Clash of Civilization?” in Foreign Affairs. Soon enough the article invites highly critical comments from several scholars. Not someone who can easily be set aside, Huntington give his response to his critics by asking a challenging question, “If not civilizations, What?” If anything the criticism only harden his conviction that civilization, instead of ideology, economy, or whatever, would become the basis of conflict in the post cold war. He doesn’t stop with this rather cynical question, he writes a book with the same subject and title, but without a question mark. Huntington, “the seeker”, has in the meantime become the “true believer” – as Eric Hoffer would have called him. He also defends his position in several interview he gives after the publication of the book.